Pluriverse in science: Discourses of Amazonian land-use change and socio-environmental (in)justice - Tello, Carlos; Neuburger, Martina (ERDKUNDE, 2023)
In the Brazilian Amazon region, social, economic, and political changing structures have increased the pressure on land, generating inequalities for the region’s most vulnerable residents. Simultaneously, scientific knowledge production has increased and documented the region’s different realities. This document presents a scientific discourse analysis of land-use change in the Amazonian region and its interaction with socio-environmental (in)justice, considering the pluriversal perspective. We respond to the main questions: Do hierarchies in scientific knowledge production contribute to silencing subaltern voices and hiding a pluriverse approach when writing about Amazonia land issues? And if so, how? A systematic literature review was conducted using the scientific dissemination platforms Scielo, Scopus, and WoS. The results show a disproportionate representation of some stakeholders, and some states are used as near-total representatives for the Amazonia region. Furthermore, consideration of pluriversal perspectives in the articles does not guarantee high sensibility for heterogeneity of local contexts or for making subaltern voices heard.